Solution Complexation Reaction Studies of a Pyrazoloisoindol Derivative Ligand by Some Metal Ions in Acetonitrile Solution - Payehghadr, Mahmood; Qezelje, Hamidreza Haghgoo; Dosangani, Farzaneh Miri; Amiri, Asghar; Hosseini, Samaneh; Hesarlo, Masoumeh Nabati; Kia, Amirsajad Soleymani (Orbital: The Electronic Journal of Chemistry, 2018)
The complexation reaction between some heavy metal ions such as: Ag+, Co2+, Hg2+, Zn2+, Ni2+, Cu2+, Cd2+, Mn2+, Cr3+, Fe3+ and Pb2+ with 2,3-dimethyl-1,2-dihydro-8H-pyrazolo[5,1-a]isoindol-8-one, ligand in acetonitrile as nonaqueous solvents at 25 ºC were investigated by spectrophotometric and conductometric methods. The formation constants (kf) of the 1:1 (metal ion to ligand) complexes were calculated by computer fitting of the absorbance-mole ratio data, and molar conductance-mole ratio data at 25 ºC using the KINFIT program, and found that complexes to vary in acetonitrile solvent in the order of Zn2+> Ag+> Cr3+> Ni2+> Hg2+> Fe3+> Cu2+> Cd2+> Co2+> Mn2+> Pb2+. DOI: http://dx.doi.org/10.17807/orbital.v10i6.1141